Testing Soil Properties and The Stability of Sedimentation Retaining Wall in Tondano Lake - Minahasa - Pangemanan, Syanne; Sudarno, Sudarno (Universitas Muhammadiyah Palu, 2019)
Analysis of technical soil properties in terms of size, type, and pressure is needed for the proper development plan. Building plans, which include Sedimentation Retaining Wall, need to be able to create buildings that are safe, stable, and resistant to both vertical and horizontal forces. It requires shear resistance analysis (PÎ±), which is carried out through laboratory tests by estimating the value of cohesion, shear angle, soil fill weight, and density. When the shear resistance analysis has a value greater than 1.5, it means that the building is resistant to force.